Long-Term Survival after Adrenalectomy for Asynchronous Metastasis of Bladder Cancer to the Bilateral Adrenal Glands - S. Washino; M. Hirai; A. Matsuzaki; Y. Kobayashi (Case Reports in Urology)
Isolated adrenal metastasis of bladder cancer, particularly the bilateral, is quite rare. Systemic chemotherapy is the treatment of choice for metastatic urothelial carcinoma. However, despite initially promising response rates of approximately 45%–71%, most tumors eventually show progression, and the median survival time following chemotherapy regimen is approximately 14-15 months. Recently, favorable results of surgery for metastatic urothelial carcinoma have been reported. Here, we report a rare case of asynchronous metastasis of bladder cancer to the bilateral adrenal glands with long-term survival after bilateral adrenalectomy. A 69-year-old man underwent radical cystoprostatectomy and ileal conduit urinary diversion for invasive bladder cancer. Ten months later, left adrenalectomy was performed for a left adrenal tumor, revealing metastatic urothelial carcinoma. After adjuvant chemotherapy, a tumor in the right adrenal gland was detected. Right adrenalectomy was done, and the tumor was also found to be metastatic urothelial carcinoma. The patient had an uneventful recovery after starting steroid replacement therapy. Three years later, he was doing well and had no evidence of recurrence. Adrenalectomy for isolated adrenal metastasis of urothelial carcinoma may be a reasonable option, even if such metastases are bilateral.